A Transparent Membrane for Active Noise Cancelation. (22nd May 2018) - Rothemund, Philipp; Morelle, Xavier P.; Jia, Kun; Whitesides, George M.; Suo, Zhigang
Abstract: A method for active noise cancelation that uses an optically transparent membrane is described. The membrane consists of a prestretched hydrophobic elastomer, attached to a rigid frame and sandwiched between two hydrogels swollen with an aqueous solution of salt. The elastomer functions as a dielectric, and the hydrogel functions as an ionic conductor. When the two hydrogels are subjected to a sinusoidal voltage, the membrane generates sound. A linear model for the reflection, transmission, and generation of sound by the membrane in an impedance tube is presented and validated. Active noise cancelation is demonstrated using the linear model and feedforward control. Compared to passive sound absorption, the sound transmission loss across the membrane is improved with active control from an average value of 7 dB to an average value of 16 dB. The transparent membrane may be used to cancel noises through a window, while maintaining its transparency. Abstract : A transparent membrane is fabricated of a stretchable dielectric membrane and ionically conducting hydrogels and vibrates when a voltage signal is applied. The vibrations can reduce the transmission of acoustic noise through the membrane. A theoretical model for the mechanical behavior of the membrane is proposed and validated. Active noise cancelation with the transparent membrane is demonstrated.